White Man Falling: Race, Gender, and White Supremacy - Ferber, Abby L. (Rowman & Littlefield Publishers, 1999)
Ferber's provocative critique examines white supremacists' firm belief that white men are becoming victims and the repercussions of their attempts to assert white male power.